Acute and Chronic Effects of High Frequency Electric Pulse Stimulation on the Akt/mTOR Pathway in Human Primary Myotubes - Valero-Breton, Mayalen; Warnier, Geoffrey; Castro-Sepulveda, Mauricio; Deldicque, Louise; Zbinden-Foncea, Hermann (Frontiers in Bioengineering and Biotechnology, 2020)
Electrical pulse stimulation (EPS) has been suggested to be a useful method to investigate the mechanisms underlying the adaptations of human skeletal muscle to both endurance and resistance exercise. Although different myotube stimulation protocols mimicking acute and chronic endurance exercise have been developed, no convincing protocol mimicking resistance exercise exists. Adaptations to resistance exercise mainly ensue via theAkt/mTOR pathway. Therefore, the aim of this study was to develop a high frequency EPS protocol mimicking resistance exercise both acutely (100 Hz, 15 V, 0.4 ms with 4 s rest between each contraction for 30 min) and chronically (acute EPS protocol repeated on three consecutive days) on human myotubes. Compared to control conditions, the acute EPS protocol increased the phosphorylation of AktSer473 at 0h (+91%, p=0.02) and 3h (+95%, p=0.01), and mTORSer2448 at 0h (+93%, p=0.03), 1h (+129%, p=0.01) and 3h (+104%, p=0.0250) post-stimulation. The phosphorylation of ERK1/2Thr202/Tyr204 was increased at 0h (+69%, p=0.02) and 3h (+117%, p=0.003) post-stimulation compared to control conditions. In addition, both S6K1Thr389 (+157%, p=0.009) and S6Ser240/244 (+153%, p=0.003) phosphorylation increased 1h after EPS compared to control conditions. Chronic EPS protocol increased the phosphorylation of S6K1Thr389 1h (+105%, p=0.03) and 3h (+126%, p=0.02) and the phosphorylation of S6Ser240/244 1h (+32%, p=0.02) after the end of the last stimulation. In conclusion, the present work shows that human muscle cells subjected to EPS can be used as an in vitro model of acute and chronic resistance exercise.